MATLAB modeling to evaluate the ratio of packed cell volume - Zena Ahmed Alwan; Suhair Mohammed Yaseen; Huda Farooq Jameel (Institute of Advanced Engineering and Science, 2021)
There are many direct and indirect methods of measuring the volumetric ratioof red blood cells relative to sample size and total blood, but the manual carcinogenic method remains the most stable and least expensive method despite the possibility of human error.The ratio percent of the packed red blood cell volume to the total volume of the blood sample is known as the packed cell volume (PCV). Our efforts were directed at finding a precise and economic method for PCV determination. There by, we designed a simple device consisting of a digital camera that is connected to a computer which uses a specific MATLAB program to process the blood images. As a result,the image can be read and the PCV can be calculated using a special code system. This new measuring system provides the capabilities and advantagesto frequently comment on measured PCV with normal or abnormal, in comparison with normal values of PCV, which are stored in the computer. Our measurement method provides accurate results compared to the ruler results to alleviate the effort of clearing the hepatitis C virus from the blood (PCV). This system enables a swift and simple sample analysis and PCV identification.